Body piercing in England: a survey of piercing at sites other than earlobe. Issue 7658 (12th June 2008) - Bone, Angie; Ncube, Fortune; Nichols, Tom; Noah, Norman D
Abstract : Objectives To estimate the prevalence of body piercing, other than of earlobes, in the general adult population in England, and to describe the distribution of body piercing by age group, sex, social class, anatomical site, and who performed the piercings. To estimate the proportion of piercings that resulted in complications and the proportion of piercings that resulted in professional help being sought after the piercing. Design Cross sectional household survey. Setting All regions of England 2005. Participants 10 503 adults aged 16 and over identified with a two stage selection process: random selection of geographical areas and filling predefined quotas of individuals. Results weighted to reflect the national demographic profile of adults aged 16 and over. Main outcome measures Estimates of the prevalence of body piercing overall and by age group, sex, and anatomical site. Estimates, in those aged 16-24, of the proportion of piercings associated with complications and the seeking of professional help. Results The prevalence of body piercing was 1049/10 503 (10%, 95% confidence interval 9.4% to 10.6%). Body piercing was more common in women than in men and in younger age groups. Nearly half the women aged 16-24 reported having had a piercing (305/659, 46.2%, 42.0% to 50.5%). Of the 754 piercings in those aged 16-24, complications were reported with 233 (31.0%, 26.8% to 35.5%); professional help was sought with 115 (15.2%, 11.8% to 19.5%); and hospital admission was required with seven (0.9%, 0.3% to 3.2%). Conclusions Body piercing is common in adults in England, particularly in young women. Problems are common and the assistance of health services is often required. Though serious complications requiring admission to hospital seem uncommon, the popularity of the practice might place a substantial burden on health services.